Honey Bees (Ben & Holly's Little Kingdom, 2017)
King Thistle needs a new jar of honey for his sandwiches, so Ben and Holly visit a buzzing bee hive to get one for him. But they soon discover that Wise Old Elf's method of collecting honey is a bit unusual . . . Read this sweet story from the Little Kingdom, and find out how Wise Old Elf gets himself out of a rather sticky situation!